2019
DOI: 10.1158/1078-0432.ccr-18-3206
|View full text |Cite
|
Sign up to set email alerts
|

irRECIST for the Evaluation of Candidate Biomarkers of Response to Nivolumab in Metastatic Clear Cell Renal Cell Carcinoma: Analysis of a Phase II Prospective Clinical Trial

Abstract: Purpose: Immune-related RECIST (irRECIST) were designed to capture atypical responses seen with immunotherapy. We hypothesized that, in patients with metastatic clear cell renal cell carcinoma (mccRCC), candidate biomarkers for nivolumab response would show improved association with clinical endpoints capturing atypical responders (irRECIST) compared with standard clinical endpoints (RECISTv1.1). Experimental Design: Endpoints based on RECISTv1.1 [objective response rate (ORR)/progression-free survival (PFS)] … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
66
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(71 citation statements)
references
References 40 publications
5
66
0
Order By: Relevance
“…High levels of CD8+ PD1+ TIM3- LAG3- TIC were associated with an activation of the inflammatory response. Interestingly, the combination of PD-L1 expression on tumor cells with the density of CD8+ PD1+ TIM3- LAG3- TIC improved the predictive value, confirming previous results from Pignon et al [ 43 , 44 ].…”
Section: Tme Components As Predictors Of Systemic Treatment Efficasupporting
confidence: 88%
“…High levels of CD8+ PD1+ TIM3- LAG3- TIC were associated with an activation of the inflammatory response. Interestingly, the combination of PD-L1 expression on tumor cells with the density of CD8+ PD1+ TIM3- LAG3- TIC improved the predictive value, confirming previous results from Pignon et al [ 43 , 44 ].…”
Section: Tme Components As Predictors Of Systemic Treatment Efficasupporting
confidence: 88%
“…The endpoints defined by RECISTv1.1 could potentially impair the identification of predictive biomarkers. For instance, in the CheckMate 010 phase II trial, tumour cell PD-L1 expression was not associated with PFS or ORR defined by RECISTv1.1, but was associated with a longer median irPFS and higher irORR using irRECIST [54]. A high level of T cells with the CD8+ PD-1+ TIM3- LAG3- phenotype, corresponding to T cell activation, was associated with longer median irPFS and higher irORR.…”
Section: Biomarkers and Their Limitationsmentioning
confidence: 99%
“…The expression of PD-1 in tumour-infiltrating lymphocytes was not associated with poor clinical outcomes [61]. If not reported alone as a biomarker in metastatic ccRCC, PD-1 was described in association with other markers to define a T cell activation phenotype correlated with the response to nivolumab [54].…”
Section: Biomarkers and Their Limitationsmentioning
confidence: 99%
“…Recently, a secondary analysis of the CheckMate 010 trial [8] was published, aimed at investigating the irRECIST criteria for the evaluation of biomarkers of response to nivolumab in mRCC patients. The different endpoints assessed according to RECIST 1.1 and irRECIST criteria were compared and the results showed that immune-related PFS (irPFS) was significantly longer than median PFS per RECIST 1.1 (5.5 versus 3.3 months), unlike ir-ORR that did not significantly differ from ORR per RECIST 1.1 (22.8% versus 21%), even though PD according to RECIST 1.1 overestimated the irPD (35.3% versus 24.6%) [58].…”
Section: Evidence In Mrccmentioning
confidence: 99%